"beaucoup plus modal que tonal": Konzepte der Tonhöhenorganisation in den Orchesterwerken von Henri Dutilleux - Wang, Ying (Die Musikforschung, 2019)
Focusing on three of Dutilleux's mid to late orchestral works - "Timbres, espace, movement ou La Nuit etoile" (1978), "The Shadows of Time" (1997) and "Sur le meme accord" (2002) - this article gives insight into Henri Dutilleux's scale-defined pitch organization techniques and the role of colour in the works of the French composer. The paper questions the ambiguous relationship between tonality and modality, and asserts the previously only peripherally attested importance of modes for Dutilleux's works. An analysis of pitch organization demonstrates how Dutilleux's aesthetic and literature-inspired concepts of "progressive growing" function musically by foregrounding pivot chords or notes, and how their return reflects the idea of involuntary memory ("memo ire involuntaire") derived from Marcel Proust's "A la recherche du temps perdu".